Aerobic power in child, cadet and senior judo athletes - Pocecco, E.; Faulhaber, M.; Franchini, E.; Burtscher, M. (Biology of Sport, 2012)
The aim of the present study was to compare performance and physiological responses during arm and leg aerobic power tests of combat duration in male child, cadet and senior judo athletes. Power output and physiological parameters, i.e., peak oxygen uptake ( ·VO2peak), peak ventilation, peak heart rate, lactate, and rate of perceived exertion, of 7 child (under 15 years: age class U15, 12.7 ± 1.1 yrs), 10 cadet (U17, 14.9 ± 0.7 yrs) and 8 senior (+20, 29.3 ± 9.2 yrs) male judo athletes were assessed during incremental tests of combat duration on an arm crank and a cycle ergometer. Children as well as cadets demonstrated higher upper body relative VO2peak than seniors (37.3 ± 4.9, 39.2 ± 5.0 and 31.0 ± 2.1 ml/kg/min, respectively); moreover, upper and lower body relative VO2peak decreased with increasing age (r = -0.575, p < 0.003 and r = -0.580, p < 0.002, respectively). Children showed lower blood lactate concentrations after cranking as well as after cycling when compared to seniors (7.8 ± 2.4 vs. 11.4 ± 2.1 mmol/l and 7.9 ± 3.0 vs. 12.0 ± 1.9 mmol/l, respectively); furthermore, blood lactate values after cranking increased with age (r = 0.473, p < 0.017). These differences should be considered in planning the training for judo athletes of different age classes.